2001
DOI: 10.1016/s0378-7753(01)00812-6
|View full text |Cite
|
Sign up to set email alerts
|

Approaches and technical challenges to high temperature operation of proton exchange membrane fuel cells

Abstract: Water loss and the coincident increase in membrane resistance to proton conduction are significant barriers to high performance operation of traditional proton exchange membrane fuel cells at elevated temperatures where the relative humidity may be reduced. We report here approaches to the development of high temperature membranes for proton exchange membrane fuel cells; composite perfluorinated sulfonic acid membranes were prepared to improve water retention, and non-aqueous proton conducting membranes were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
405
3
3

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 609 publications
(417 citation statements)
references
References 21 publications
6
405
3
3
Order By: Relevance
“…At variance with previous results on porous glass [16] it has been shown, for the first time as far as we know [3], that thin film alumina membranes can be used as template for ionic conductor membrane allowing to fabricate different assemblies to be used in different types of fuel cell. The easy preparation of alumina membranes also in large area, their low production cost and wide range of thermal stability could make them attractive for more economically viable fuel cell by allowing to increase the working temperature of the fuel cell and the use of less expensive catalyst.…”
Section: Discussioncontrasting
confidence: 73%
“…At variance with previous results on porous glass [16] it has been shown, for the first time as far as we know [3], that thin film alumina membranes can be used as template for ionic conductor membrane allowing to fabricate different assemblies to be used in different types of fuel cell. The easy preparation of alumina membranes also in large area, their low production cost and wide range of thermal stability could make them attractive for more economically viable fuel cell by allowing to increase the working temperature of the fuel cell and the use of less expensive catalyst.…”
Section: Discussioncontrasting
confidence: 73%
“…The better performance of the SPEEK/PSf-ABIm blend membrane compared to that of the plain SPEEK and Nafion membranes could be attributed, respectively, to the promotion of proton conduction through acid-base interaction and lower methanol crossover (see below). Furthermore, while it is difficult to get fuel cell performance data with membranes containing imidazole due to the poisoning of the Pt catalyst by imidazole [21], the tethering of N-heterocycles like 2-amino-benzimidazole to a polymer backbone prevents or suppresses such a poisoning. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Higher operating temperatures mean that water management is simplified significantly as there is only a single (gaseous) phase present. This means that the transport of water in the membrane, electrodes and diffusion layer is easier and flow field plate design can be greatly simplified [10,11,13]. Another effect of the higher temperatures is that the reactant and product gases are expected to have increased diffusion rates [9] and with no liquid water present to block the electrochemically active surface area thus allowing for more reactions to occur.…”
Section: Heat and Water Managementmentioning
confidence: 99%
“…with a superprotonic temperature of 140 o C. As early as 2001 this class of membranes was reported in Nature [73] when it was first tested in a fuel cell at 150e160 o C and more recent studies showed conductivity of 0.04 S cm -1 at 200 o C [13], and blending with microporous zeolite improved conductivity [74]. However, the published single cell performance for these materials is poor.…”
Section: Polymer Electrolyte Membrane (Pem)mentioning
confidence: 99%